The Importance of the Covid-19 Vaccination in Children Ages 6-11 Years at Primary School 4 Limboto Gorontalo Regency - Andi Akifa Sudirma; Dewi Modjo (Journal of Universal Community Empowerment Provision, 2022)
Children aged 6 to 12 years are the age of children entering elementary school. Children are one of the age groups that are vulnerable to being infected with Covid-19, therefore, to break the chain of transmission of the Covid-19 virus, children must be equipped with the knowledge of how important it is to vaccinate against COVID-19. This is the goal of community service activities, namely to increase children's knowledge about the importance of vaccinating covid-19 and also being able to understand the impact of not vaccinating covid-19. The method used is education using Power Point, Banner and Leaflet. The results achieved with this activity, SDN 4 Limboto, were very supportive in carrying out this activity, a series of activities were carried out to achieve good results because 35 children participated in the counseling. Conclusion: in breaking the chain of transmission of covid-19, children must first be educated about the importance of vaccination and the impact of not vaccinating against covid-19. This also requires the role of the parents and also the school.